The comparative research of kidneys of rainbow trout (Oncorhynchus mykiss, Walbaum 1792) and rat (Rattus norvegicus, Berkenhout 1769) in morphometric and histologic manner - (:unkn) unknown (My University, 2006)
In this research, the Rainbow Trout (Oncorhynchus mykiss, Walbaum 1792) and Wistar Albino Rat (Rattus norvegicus, Berkenhout 1769) are chosen vertebrates living in different media. It is seen that fish and rat kidneys differ in morphologic and histologic structures. Fish kidney consists of two different parts as head and body, whereas rat kidney has a more complicated and developed structure. After the examination of the sections taken from the kidney tissues, it is realized that the fish cortex and medulla shows difference with that of mammals in structure. Also, fish do not have a stable nefron system as in mammals and have different nefron structures in terms of structure and function. From the data obtained, it is observed that the fish kidney lacks the Henle part-which is a characteristic of developed vertebrates-it has more concentrated hematophoitic tissues and it has a different nefron structure. © 2006 Asian Network for Scientific Information.
Keywords: Kidney; Rainbow trout; Rat